Sudden Death: The Unseen Danger of Tuberculosis - Syed Affridh; Ganesh Rajahan; Venkatesan M.; Sneha S.; Priyadarshee Pradhan (Indian Journal of Forensic Medicine and Pathology, 2026)
Tuberculosis still remains a major global health problem, especially in developing countries. Death and prevalence of tuberculosis has been reported worldwide. Tuberculosis usually presents primarily as lung disease with dissemination to the intestines increasing its morbidity. But the challenging part is its vague symptoms. Sudden death following intestinal TB is rare. A case involving a 24-year-old woman was received unconscious at the emergency department with compliants of severe stomach pain and vomiting. Despite resuscitative measures, she was declared dead. The postmortem examination revealed a white, cheese-like area at the apex of her right lung. Thickened dark tissue noted over the ileocecal junction. Histopathology confirmed tuberculosis in both lungs and intestines. Intestinal obstruction was noted at the site of TB involvement. This case highlights the importance of recognizing severe forms of intestinal tuberculosis This case underlines the vital role of precise medicolegal autopsy and complete histopathological examination in identifying hidden causes of sudden death.